Bridging Urban Mobility Gaps: Integrating Rapid Transit Railways into Lusaka City’s Transport Network - Mwiza Nalomba; Erastus Misheng’u Mwanaumo; Penjani Hopkins Nyimbili; Wellington Didibhuku Thwala (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
This study explores the feasibility of a rapid transit railway system to address Lusaka City's growing transportation challenges caused by rapid urbanization and population growth. The research proposes the Chongwe-Kafue line through Lusaka to enhance urban mobility.  Using Google Earth and QGIS for station identification, mapping and distance analysis, the study delineates a 92.8 km main corridor with 13 branch-off lines spanning 51.6 km, including two direct airport connections, designed to enhance accessibility and efficiency. Travel time analysis, based on Delhi Metro’s operational model, estimates a 105.6-minute journey with an average speed of 60 km/h. Additionally, fare structures and construction costs were evaluated. The findings demonstrate the system's viability as an efficient alternative to minibus-dominated transport, offering reduced travel times and improved connectivity, stimulating economic growth and supporting sustainable urban development. This research provides a practical framework for policymakers and urban planners to implement a feasible transit solution in Lusaka.